Reduced Presence of SARS-CoV-2 microRNA-like Small RNA in the Serum of Patients with Post-Acute Sequelae SARS-CoV-2 Infection - Maria Alfreda Stincarelli; Isabella Abbate; Giulia Matusali; Michele Tanturli; Marta Camici; Rosaria Arvia; Elisabetta Lazzari; Eleonora Cimini; Alessandra Vergori; Fabrizio Maggi; Simone Giannecchini (Microorganisms)
The mechanisms underlying post-acute sequelae of SARS-CoV-2 infection (PASC) are a topic of debate. This study examined the presence of SARS-CoV-2 microRNA (miRNA)-like small RNAs in extracellular fluids and their potential link to PASC by using a quantitative stem-loop RT-PCR MiRNA assay. Initially, it was demonstrated that three previously identified SARS-CoV-2 miRNA-like small RNAs, specifically svRNA 1 and 2 and miR-07a, were significantly expressed in infected cells in vitro and released into the supernatant following infection by different SARS-CoV-2 variants. Then, the expression of three SARS-CoV-2 small RNAs was studied in both nasopharyngeal swabs (NPS) and sera from 24 patients at their initial COVID-19 diagnosis (T0) and in sera collected 91 to 193 days post-diagnosis (T1). Notably, 11 out of 24 patients (46%) reported PASC consequences. All NPS samples showed SARS-CoV-2 small RNA expression with an altered cytokine network during acute infection, but it did not correlate with PASC outcomes. Serum samples had similar small RNA statuses, though PASC patients, notably at T1, but not at T0, displayed reduced overall positivity compared to those without PASC. The host target expression of SARS-CoV-2 small RNAs was not significantly different between groups. This suggests a need for further research into SARS-CoV-2 small RNA and its role in viral behavior and PASC consequences.